Community plantation forests in Indonesia: Challenges and policy recommendations - Kartodihardjo, H.; Nugroho, B.; Rohadi, D.; Suharjito, D.; Dermawan, A. (Center for International Forestry Research, 2011)
The Ministry of Forestry’s community plantation forests programme, established in 2007, aims to provide communities with access to forest resources. Despite government support in policies and funding the programme has fallen far short of its targets. Researchers interviewed stakeholders at national and local levels to identify obstacles to success and steps to ease the way forward. We have four main recommendations for the Ministry of Forestry and several others detailed in the conclusions. To increase the success of the CPF programme, the Ministry of Forestry could: simplify land designation and permitting processes, reducing transaction costs for smallholder farmers; facilitate access to loans and make loan size more flexible to serve smallholders familiar with IDR 1–2 million loan schemes; expedite community timber transportation and better access to markets through coordination with provincial and district forestry offices; coordinate with district forestry offices to establish forestry extension activities to improve stand quality and yield.